2012
DOI: 10.1063/1.4738980
|View full text |Cite
|
Sign up to set email alerts
|

What are the most efficient basis set strategies for correlated wave function calculations of reaction energies and barrier heights?

Abstract: As electronic structure methods are being used to obtain quantitatively accurate reaction energies and barrier heights for increasingly larger systems, the choice of an efficient basis set is becoming more critical. The optimum strategy for achieving basis set convergence can depend on the way that electron correlation is treated and can take advantage of flexibility in the order in which basis functions are added. Here we study several approaches for estimating accurate reaction energies and barrier heights f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(61 citation statements)
references
References 76 publications
(83 reference statements)
3
57
1
Order By: Relevance
“…The E Barrier obtained with the three extrapolation schemes are in agreement with each other within 0.2 kcal.mol −1 (Table ). It has been shown that the extrapolation to CCSD(T)/CBS with additive schemes, using the aug‐cc‐pVDZ basis set to evaluate the correlation energy difference between MP2 and CCSD(T), has very small errors (circa 0.6 kcal.mol −1 for E Barrier ) when compared with the CCSD(T)‐F12a/apr‐cc‐pV(5 + d)Z level of theory . As reference energy, we used the mean of the E Barrier and E R given by the three schemes, 22.1 kcal.mol −1 and −3.0 kcal.mol −1 , respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…The E Barrier obtained with the three extrapolation schemes are in agreement with each other within 0.2 kcal.mol −1 (Table ). It has been shown that the extrapolation to CCSD(T)/CBS with additive schemes, using the aug‐cc‐pVDZ basis set to evaluate the correlation energy difference between MP2 and CCSD(T), has very small errors (circa 0.6 kcal.mol −1 for E Barrier ) when compared with the CCSD(T)‐F12a/apr‐cc‐pV(5 + d)Z level of theory . As reference energy, we used the mean of the E Barrier and E R given by the three schemes, 22.1 kcal.mol −1 and −3.0 kcal.mol −1 , respectively (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We use CCSD(T)-F12a, which is explicitly correlated coupled cluster theory with single and double excitations and a quasiperturbative treatment of connected triple excitations, 47 with the jun-cc-pVTZ 48 …”
Section: Choice Of Electronic Structure Methodsmentioning
confidence: 99%
“…There are then two ways to obtain accurate energies: (a) solution of the SE after explicit introduction of correlation in the wave function (2) via r i j coordinates and (b) exploitation of the convergence of hierarchized correlation-consistent basis sets toward the CBS limit. Although this may conceivably become a matter of merely historical interest (28), with standard CCSD(T) calculations giving way to their explicit correlated counterparts, any analysis of the current literature or direct comparison of standard versus explicitly correlated methods (generally denoted by R12) shows such a scenario to be far away, since R12 methods are relatively new, with even analytical derivatives being largely unavailable (29). Actually, despite a fast convergence (∝ X −7 ), R12 methods perform inefficiently with small basis sets (2).…”
Section: Explicit Correlation Versus Complete Basis Set Extrapolationmentioning
confidence: 99%